Pasteurized Akkermansia muciniphila Timepie001 ameliorates DSS-induced ulcerative colitis in mice by alleviating intestinal injury and modulating gut microbiota - Han, Huan; Xiong, Hui; Liu, Zengli; Liu, Xunzhi; Wang, Hailin; Kou, Jiaxiang; Yi, Dewei; Shi, Ying; Wu, Hao; Qiao, Jianjun (Frontiers in Microbiology, 2025)
IntroductionAkkermansia muciniphila (A. muciniphila), known as a next-generation probiotic, has been widely recognized for its beneficial effects in various metabolic diseases. While there is not much research whether live or pasteurized A. muciniphila has different effects on intestinal health.MethodsIn the present study, a strain of A. muciniphila was isolated from healthy individuals, with the live and pasteurized A. muciniphila named Timepie001 and Timepie001+, respectively. They were administered to dextran sulfate sodium-induced ulcerative colitis mice to investigate their influences on the host intestinal health.Results and conclusionThe results showed that prophylactic supplementation with live and pasteurized A. muciniphila alleviates ulcerative colitis symptoms by retarding weight loss, preserving intestinal tissue structure, modulating inflammatory cytokines (TNF-α, IL-1β), and enhance the colonic mucosal barrier by upregulating the expression of tight junction protein Claudin-1. Interestingly, pasteurized A. muciniphila has a better effect compared with live A. muciniphila. Moreover, pasteurized A. muciniphila can regulates the gut microbiome to maintain intestinal homeostasis. This provides theoretical support for the widespread application of postbiotics in the food industry.